Characteristic of downstream water thrust in pico-scale hydropower based on screw turbine - Eswanto, .; Siman, .; Muhammad Nuh Hudawi, Pasaribu; Mohd Adnin, Hamidi
The aim of this research is to determine the characteristics of water flow that occurs on the downstream side.The abundance of water is an advantage that can be utilized by mankind and especially for living creatures to continue life. An energy source that is still abundant and can be profitable in helping human work is water which can be used in generators to produce electricity. Hydropower is a type of generator that is environmentally friendly and easy to manufacture, provided there is a continuous flowing water source. This research focuses on picohydro scale plants, where this hydropower model can produce electricity even if the water flow is small. The research method is by direct experimentation from a prototype device on pico-hydro hydropower. In the initial stage, all measuring instruments are installed as planned and after that they are calibrated before trials are carried out in data collection. The next stage continues with the testing and measurement process to obtain the desired data. The test model used uses a screw turbine with a total of 5 windings. The results of the research show that the water pressure that reaches the downstream part does not all go straight out and leave the turbine housing, this condition is because the water partially accumulates in the body of the turbine housing where it collides with each other on the right and left sides. turbine house. The characteristics of water thrust are influenced by a number of moments, water thrust force, water pressure and water speed, each of which depends on the flow of water entered into the turbine housing to push the screw turbine blades.